The Septuagint's translation of the Hebrew verbal system in Chronicles - Good, Roger (Supplements to Vetus Testamentum ;, 2010)
This book is the first detailed investigation of the translation of the Hebrew verbs of Chronicles into Greek, especially from the perspective of two diachronic developments: that of the Hebrew verbal system and that of the trend toward a more literal translation of the Bible. The translation provides a view of the Hebrew verbal system in the Hellenistic period (approx. 150 BCE) as part of the continuum in the development of the Hebrew verbal system from classical biblical Hebrew to Mishnaic Hebrew. The translation also testifies to the trend in the process of the translation of the Bible from.